A Biopsychosocial Approach to Understanding Panic Buying: Integrating Neurobiological, Attachment-Based, and Social-Anthropological Perspectives - Rajkumar, Ravi Philip (Frontiers in Psychiatry, 2021)
The global COVID-19 pandemic has focused the attention of researchers, civil authority and the general public on the phenomenon of "panic buying", characterized by the excessive purchase of specific materials - particularly food and hygiene-related products - in anticipation of an expected shortage. This phenomenon has been well documented in response to several natural and man-made disasters, but its global scope and severity in the context of COVID-19 are unprecedented. This response can negatively impact health, food security and disease prevention efforts. Attempts to modify such behaviours are more likely to succeed if they are based on insights from both the biomedical and the social sciences. From a biological perspective, the phenomenological overlap between panic buying and psychological disorders such as hoarding disorder and compulsive buying raises the possibility of a shared neurobiological underpinning. Evolutionary models suggest that these behaviours represent an attempt to enhance individual and group survival in the face of a threatened scarcity of resources. These phenomena may be influenced by specific genetic variants which are also implicated in hoarding-related psychological disorders. From a psychological perspective, attachment theory provides a conceptual framework that serves as a bridge between prior life adversity, current deprivation, and an increased attachment to material objects. Such a framework is of relevance when considering panic buying during the COVID-19 pandemic, which has been associated with significant disruptions in attachment bonds . From a social-anthropological perspective, hoarding and related behaviours have been associated with social exclusion and rejection, as well a lack of social support. These risk factors have affected large sections of the general population in the context of the COVID-19 pandemic and the governmental responses to it. This perspective also emphasizes the symbolic significance of the hoarded objects themselves. In this paper, an attempt is made to integrate these three perspectives and thereby formulate a biopsychosocial model of panic buying in response to this global health crisis. The existing scientific literature on panic buying is examined in the light of this model. Finally, suggestions are proposed as to how this model might inform social strategies aimed at preventing or reducing panic buying.